Müller Glia maintain their regenerative potential despite degeneration in the aged zebrafish retina. Issue 4 (22nd March 2022) - Martins, Raquel R.; Zamzam, Mazen; Tracey‐White, Dhani; Moosajee, Mariya; Thummel, Ryan; Henriques, Catarina M.; MacDonald, Ryan B.
Abstract: Ageing is a significant risk factor for degeneration of the retina. Müller glia cells (MG) are key for neuronal regeneration, so harnessing the regenerative capacity of MG in the retina offers great promise for the treatment of age‐associated blinding conditions. Yet, the impact of ageing on MG regenerative capacity is unclear. Here, we show that the zebrafish retina undergoes telomerase‐independent, age‐related neurodegeneration but that this is insufficient to stimulate MG proliferation and regeneration. Instead, age‐related neurodegeneration is accompanied by MG morphological aberrations and loss of vision. Mechanistically, yes‐associated protein (Yap), part of the Hippo signalling, has been shown to be critical for the regenerative response in the damaged retina, and we show that Yap expression levels decline with ageing. Despite this, morphologically and molecularly altered aged MG retain the capacity to regenerate neurons after acute light damage, therefore, highlighting key differences in the MG response to high‐intensity acute damage versus chronic neuronal loss in the zebrafish retina. Abstract : Our data show that aged, molecularly and morphologically altered MG can still be stimulated to regenerate in response to an acute damage, highlighting key differences in MG response when compared to the chronic damage in ageing.